Thailand's Compliance in 2017-2022 with the ASEAN Convention Against Trafficking in Persons, Especially Women and Children - Safiinatunnajah, Humaira; Saraswati, Dini Putri (Jurnal Studi Diplomasi dan Keamanan, 2025)
Thailand is one of the countries in the Southeast Asia region with quite high cases of human trafficking, either as a destination country, sending country, or transit country. According to this, Thailand seeks to combat human trafficking through its implementation of the ASEAN Convention Against Trafficking in Persons, Especially Women and Children which is implemented as a reference for their national agenda. In this qualitative research, the 4Ps are seen as the key points, including prevention, protection, prosecution, and partnership. The commitment implemented by Thailand in the 2017-2022 period is a form of compliance to combat human trafficking through the international regime. This is also used as an effort to maintain stability, specifically in national security and particularly in regional security, namely through a number of prevention strategies to the community, facilitating protection for victims, fulfilling justice for victims by prosecuting perpetrators, and strengthening synergy between institutions in its implementation. Keywords:  Human Trafficking, Security, ASEAN, Thailand